"Harder", "better", "faster", "greener" : a China e os Estados Unidos na corrida pelas tecnologias energéticas verdes - Corrêa, Lucas, 1991- (2024)
Orientadores: Antonio Carlos Diegues Junior; Renato de Castro Garcia